The Genetic Variation Analysis of Temulawak (Curcuma xanthorrhiza Roxb.) In Java Island Using Random Amplification of Polymorphic DNA (RAPD) Method - Daryono, Budi Setiadi (2011)
Temulawak (Curcuma xanthorrhiza Roxb.) or Javanese Turmeric is originated from Indonesia and found throughout Java Island, Bali, and Moluccas. In Indonesia, Temulawak is used as a traditional medicine to cure various diseases. However, not many researches on the genetic variation of Temulawak have been conducted, especially the genetic variation of Temulawak throughout Java Island. Such research is important to be done for promoting Temulawak nationally and internationally as a platinum variety originated from Indonesia. Therefore, this research was aimed to analyze the genetic variation of Temulawak found in some areas in Java Island. The method used was Random Amplification of Polymorphic DNA (RAPD). Eleven DNA samples of Temulawak were isolated from Nganjuk (East Java), Kulonprogo (Yogyakarta), Kediri (East Java), Karanganyar (Central Java), Boyolali (Central Java), Tasikmalaya (West Java), Purworejo (Central Java), Imogiri (Yogyakarta, labeled as Local variety), Trenggalek (East Java, labeled as Bathok Variety), Pogung (Yogyakarta), and Kadisoka Village (Yogyakarta). Those DNAs were then amplified using Polymerase Chain Reaction (PCR) with arbitrary primers. The PCR results then were scored and analyzed using NTSYS -pc 21 version 2.1.1 Software. The results revealed that all of samples were divided into three main clusters based on their genetic relatedness. The first cluster consisted of Temulawak from Nganjuk, Kulonprogo, Kediri, Karanganyar, Boyolali, and Tasikmalaya. Those varieties had a close genetic relatedness and might be originated from one variety of Temulawak. The second cluster was only consisted of samples from Purworejo, which means that Temulawak from Purworejo is genetically distinct from the rest of the samples. The third cluster consisted of Temulawak from Pogung and Kadisoka Village which they are closely related. It could be concluded that the genetic variation of Temulawak in Java is divided into three genetic clusters. Keywords: Temulawak, Genetic Variation, RAPD